Energy and exergy analysis of the performance of 10 TR lithium bromide/water absorption chiller - Alvaro Antonio Ochoa Villa; José Carlos Charamba Dutra; Jorge Recarte Henriquez Guerrero (Revista Técnica de la Facultad de Ingeniería)
This work aims at the theoretical study on the performance of an single stage absorption chiller (LiBr- H2O), driven by hot water. A mathematical model was developed based on the principles of energy conservation, entropy, mass and species, by various functions for determining the thermophysical properties, and transfer coefficients of heat exchangers. The model equations were solved in EES-32 program (engineering equation solver version 32). The program data generated by the variation of the inlet temperature of hot water were used for the determination of a range of values of energy and exergy COP system whose maximum were 0.7406 and 0.2409, respectively. The model was also able to assess the influence of temperature and solution concentration of the absorption machine. The analysis revealed that the main irreversibilities were found in the cooling tower, generator and absorber, with values of 34, 32 and 16% respectively. The lower level of the irreversibility of the system was found in the solution pump with 1% relative to the total value of the system.